THE IMPACT OF PARENTS DIVORCED TOWARDS CHILDREN IN NICHOLAS SPARKS’ THE LAST SONG - Pepah, Andrew; Mogea, Tini; Maukar, Merlin (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The purpose of this study was revealed about impacts of parents’ divorced towards children revealed in Nicholas Spark’s The Last Song. This study delimited only in revealed about the impact of parents’ divorced toward child through the character of children itself in Nicholas Spark’s The Last Song. In this research the writer used qualitative method in analyzing the novel. The writer used two kinds of sources in collecting the data in this research. That is primary source and secondary sources. Novel The Last Song by Nicholas Sparks is the primary source and the other references which have relation with the story to support the writer to completing the data is secondary source. In analyze the data the writer used objective.It means that the study was focused on the work. Based on the previous chapter, the researcher concludes that there are three main impacts from parents divorced towards child reflected from Ronnie Miller as a daughter in her divorced family. Those are: difficulties adaption to change, emotionally sensitive and feeling of guilt. Parents divorce can be a difficult time for a family. Not only are the parents realizing new ways of relating to each other, but they are learning new ways to parent their children. When parents divorce, the effects of divorce on children can vary. Some children react to divorce in a natural and understanding way, while other children may struggle with the transition